2022
DOI: 10.1055/s-0042-1742724
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Standard Treatment Approaches in Locoregionally Advanced Nasopharyngeal Carcinoma

Abstract: Objectives To compare outcomes and toxicity of two standard treatment approaches of advanced nasopharyngeal carcinoma (NPC). Methods Between 2010 and 2016, patients with NPC, stage II–IVa, treated with induction chemotherapy (IC) (TPF), followed by concurrent chemoradiotherapy (CCRT) (induction group), or CCRT, followed by adjuvant chemotherapy (AC) (PF) (no-induction group), were retrospectively reviewed. CCRT included platinum-based chemotherapy with intensity-modulated radiotherapy. Survival out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Both groups had similar compliance rates for radiotherapy and chemotherapy, but the IC group experienced fewer toxic effects during CCRT such as nausea, dermatitis, mucositis, swallowing, and dryness. These ndings provide further evidence in support of previous studies indicating that the survival outcomes after IC + CCRT are consistent with those after CCRT + AC 23,24,30 , while toxic side effects were increased during CCRT 19,20,[31][32][33] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Both groups had similar compliance rates for radiotherapy and chemotherapy, but the IC group experienced fewer toxic effects during CCRT such as nausea, dermatitis, mucositis, swallowing, and dryness. These ndings provide further evidence in support of previous studies indicating that the survival outcomes after IC + CCRT are consistent with those after CCRT + AC 23,24,30 , while toxic side effects were increased during CCRT 19,20,[31][32][33] .…”
Section: Discussionsupporting
confidence: 89%
“…Their results indicated that the IC + CCRT group achieved a similar rate of 5 diseasefree survival(DFS) at 69.8% compared with the CCRT + AC group which had a corresponding rate of 65.6%. Another retrospective study showed that survival outcomes were comparable between IC + CCRT and CCRT + AC groups 24 .…”
Section: Introductionmentioning
confidence: 99%